Growth and dry matter partition wheat plants in response to seed vigor and water restriction - Koch,Felipe (2021)
Abstract: The quality of the seeds and the occurrence of stresses are decisive for the development of the crops. Thus, the work aimed to verify the effect of seed vigor on growth and dry weight partition of wheat plants subjected to water stress. For growth evaluation, the experimental design was completely randomized, in a 2 x 2 x 8 factorial scheme (vigor level x water regime x collection time), with four replications. To evaluate the yield of the seeds, the design was completely randomized, in a 2 x 2 factorial scheme (level of vigor x water regime), with four replications. Total dry weight, dry weight production rate, relative growth rate, leaf area ratio, leaf area, solar energy conversion efficiency, dry weight partition and harvest index were evaluated. Total dry weight production, dry weight production rate, leaf area, leaf weight ratio, solar energy conversion efficiency and yield were higher for plants from highly vigorous seeds under field capacity. The yield was higher for plants with high vigor compared to those with low vigor in field capacity.